2020
DOI: 10.1099/mgen.0.000448
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability in an interspecific hybrid of the genus Saccharomyces: a matter of adaptability

Abstract: Ancient events of polyploidy have been linked to huge evolutionary leaps in the tree of life, while increasing evidence shows that newly established polyploids have adaptive advantages in certain stress conditions compared to their relatives with a lower ploidy. The genus Saccharomyces is a good model for studying such events, as it contains an ancient whole-genome duplication event and many sequenced Saccharomyces cerevisiae are, evolutionary speaking, newly formed polyploids. Many polyploids have unstable ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Saccharomyces cerevisiae is one of the descendants of this ancestral hybridization event, currently maintaining a third of its genome in duplicate [5,6,10]. In more recent works, it has been demonstrated that hybridization events among wine yeasts are produced mainly through rare mating types, giving rise to new hybrids with differential duplicated chromosome retention linked to adaptive functional innovation [11][12][13]. These works support the prevalence of duplicates and innovative potential as proposed more than fifty years ago by Ohno [14].…”
Section: Introductionsupporting
confidence: 57%
“…Saccharomyces cerevisiae is one of the descendants of this ancestral hybridization event, currently maintaining a third of its genome in duplicate [5,6,10]. In more recent works, it has been demonstrated that hybridization events among wine yeasts are produced mainly through rare mating types, giving rise to new hybrids with differential duplicated chromosome retention linked to adaptive functional innovation [11][12][13]. These works support the prevalence of duplicates and innovative potential as proposed more than fifty years ago by Ohno [14].…”
Section: Introductionsupporting
confidence: 57%
“…However, studies comparing Saccharomyces strains rarely address the “founder effect” of using a subclone lineage of a strain (due to methodological constraints) to characterize the strain itself. Only a few studies have focused on heterogeneous subclone lineages as well as cryptic variation of the PE‐2 bioethanol strain or its derivative JAY270 (Reis et al, 2014; Rodrigues‐Prause et al, 2018; Sampaio et al, 2019) and those of the lager W34/70 strain (Bolat et al, 2008; van den Broek et al, 2015), as well as on lineages on the VIN7 commercial hybrid wine starter yeast (Morard et al, 2020), whereas in most other cases, strains are used interchangeably with subclone lineages in literature. In fact, the commonly used and well‐known tetraploid Ale strain has been sequenced and analyzed by three recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clades have become adapted to the production of fermented beverages or foods, and these are regarded as prime examples of microbe domestication that quite often led to the existence of polyploid and/or aneuploid lineages (Duan et al, 2018; Gallone et al, 2016; Peter et al, 2018; Steensels et al, 2019; Strope et al, 2015). The most widespread yeast‐fermented product worldwide that uses a different yeast “species” is lager beer, where fermentation is carried out by domesticated hybrids of S. cerevisiae and Saccharomyces eubayanus (known as Saccharomyces pastorianus and Saccharomyces carlsbergensis as well), whereas hybrids of other combinations have also been found in several fermentation industries (Gallone et al, 2019; Langdon et al, 2019; Morard et al, 2020; Salazar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we used a novel approach to demonstrate that self-fertile isolates of different Ceratocystis species can hybridize and that their progeny often bears the mitochondria of both parental species. Although the importance of hybridization during adaptation and evolution is widely recognized [ 45 , 46 ], fungal hybridization is not completely understood, and few studies have explored the level to which sexual reproductive barriers and species boundaries are permeable [ 47 , 48 ]. By employing cultures grown from single ascospore drops obtained from crosses between C. fimbriata and C. manginecans and between C. fimbriata and C. eucalypticola, we showed, for the first time, that self-fertile isolates of closely related Ceratocystis species can sexually reproduce, forming viable progeny with mitochondrial inheritance from both parents.…”
Section: Discussionmentioning
confidence: 99%